Environmental and anthropogenic drivers of watercress (Nasturtium officinale) communities in char-lands and water channels across the Swat River Basin: implication for conservation planning - Khan, Nasrullah; Ullah, Rafi; Okla, Mohammad K.; Abdel-Maksoud, Mostafa A.; Saleh, Ibrahim A.; Abu-Harirah, Hashem A.; AlRamadneh, Tareq Nayef; AbdElgawad, Hamada (Frontiers in Plant Science, 2023)
Recent anthropogenic sources and excess usage have immensely threatened the communities and habitat ecology of this region's medicinally and economically significant crops. Therefore, our study aims to evaluate the community structure and related environmental characteristics sustaining Nasturtium officinale communities along the river basin (RB) in North-West Pakistan, using the clustering procedure (Ward's method) and Redundancy analysis (RDA). From 340 phytosociological plots (34 ×10 = 340), we identified four ecologically distinct assemblages of N. officinale governed by different environmental and anthropogenic factors for the first time. The floristic structure shows the dominance of herbaceous (100%), native (77%), and annual (58.09%) species indicating relatively stable communities; however, the existence of the invasive plants (14%) is perturbing and may cause instability in future resulting into the replacement of herbaceous plant species. Likewise, we noticed apparent variations in the environmental factors, i.e. clay percentage (P = 3.1×10-5), silt and sand percentage (p < 0.05), organic matter (p < 0.001), phosphorus 31 and potassium (p < 0.05) and heavy metals, i.e. Pb, Zn and Cd (p < 0.05) indicating their 32 dynamic role in maintaining the structure and composition of these ecologically distinct 33 communities. RDA has also demonstrated the fundamental role of these factors in 34 species-environment correlations and explained the geospatial variability and plants' 35 ecological amplitudes in the Swat River wetland ecosystem. We concluded from this 36 study that N. officinale communities are relatively stable due to their rapid colonization; 37 however, most recent high anthropogenic interventions especially overharvesting and 38 sand mining activities, apart from natural enemies, water deficit, mega-droughts and 39 recent flood intensification due to climate change scenario are robust future threats to 40 these communities. Our research highlights the dire need for the sustainable uses and 41 conservation of these critical communities for aesthetics, as food for aquatic macrobiota 42 and humans, enhancing water quality, breeding habitat, fodder crop and its most 43 promising medicinal properties in the region.